2012
DOI: 10.1002/hed.23055
|View full text |Cite
|
Sign up to set email alerts
|

Dysphonia as an unusual debut of parsonage–Turner syndrome

Abstract: The case illustrates the need for a careful clinical-neurologic examination beyond the larynx in patients presenting with idiopathic dysphonia. Parsonage-Turner syndrome should be considered as one of the rare causes in the differential diagnosis of isolated and otherwise unexplained dysphonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…In its common form, NA involves the brachial plexus, with frequent impairment of the suprascapular, anterior interosseous, or long thoracic nerves . NA may also involve the cranial nerves (CNs), although more frequently in its hereditary form . Despite the lack of familial disease, hereditary NA cannot be ruled out in our patient, as we did not perform genetic testing.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In its common form, NA involves the brachial plexus, with frequent impairment of the suprascapular, anterior interosseous, or long thoracic nerves . NA may also involve the cranial nerves (CNs), although more frequently in its hereditary form . Despite the lack of familial disease, hereditary NA cannot be ruled out in our patient, as we did not perform genetic testing.…”
Section: Discussionmentioning
confidence: 88%
“…In hereditary NA, impairment outside the brachial plexus occurred in up to 55.8% of patients, with involvement of the recurrent laryngeal nerve reported in 18.6% . Involvement of the CNs may either be isolated or associated with plexopathy, and the onset of symptoms can occur in either the CN(s) or the upper limb(s) . Usually, several CNs are affected simultaneously, with impairment of a combination of nerves IX, X, XI, and XII or bilateral VII .…”
Section: Discussionmentioning
confidence: 99%
“…There are no studies in the literature showing the incidence of ENA with laryngeal paralysis. Among the existing cases, the most recent one was that of a patient in Spain, 65 years of age, female, with paralysis of the right vocal fold as the first manifestation of ENA (16) . After 8 weeks under expectant conduct, there was partial improvement of the dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…In the voice therapy conducted, the main vocal techniques used were yawn-sigh (12) and inspiratory phonation (13) , to eliminate the paralytic falsetto and to reduce the compensatory unilateral median constriction; prolonged /b/ (14) and emission issued with hand over the mouth (15) , aiming at the reestablishment of neural function of the right vocal fold of the patient. As described in the literature, cases of paralytic falsetto should be immediately treated, with the completion of intensive speech-language pathology and audiology therapy (16) . In the present case, the frequency of the exercises, five times a day, was adapted to the routine of the patient, who would wake up after 12 hours due to his engagements as a musician.…”
Section: Discussionmentioning
confidence: 99%
“…Tsao et al reviewed medical records of 33 cases of idiopathic phrenic nerve paralysis and found that 17 patients had clinical features of NA [ 18 ]. A patient that developed unilateral recurrent laryngeal nerve palsy one week before shoulder pain and amyotrophy was recently reported [ 20 ]. Wurmser and Kaeser described a patient who developed unilateral recurrent laryngeal nerve palsy 7 months before shoulder pain and amyotrophy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%